2009
DOI: 10.1177/1359104508100137
|View full text |Cite
|
Sign up to set email alerts
|

Guilt and Posttraumatic Stress Symptoms in Child Victims of Interpersonal Violence

Abstract: Our objective was to examine the relationship between guilt and posttraumatic stress disorder (PTSD) symptoms in children with a history of interpersonal violence. Eighty-seven children between the ages of 5 and 16 years (mean age = 11.70 years) were administered the Clinician-Administered PTSD Scale for Children and Adolescents to assess for PTSD symptoms and associated features. Multiple regression analysis found that guilt over acts of commission or omission (behaviors the child performed or failed to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…The literature on adults exposed to different forms of interpersonal trauma has shown links between shame appraisals and posttraumatic stress symptoms (Andrews, Brewin, Rose, & Kirk, 2000;Beck et al, 2011;La Bash & Papa, 2013;Wilson et al, 2011); self-blame appraisals and depression symptoms (Flicker, Cerulli, Swogger, & Talbot, 2012;Hassija & Gray, 2012;Hazzard, 1993;Kaysen, Scher, Mastnak, & Resick, 2005); betrayal appraisals and dissociation symptoms (DePrince et al, 2011;Smith & Freyd, 2013); and alienation appraisals and posttraumatic stress symptoms (DePrince et al, 2011). Among youth exposed to interpersonal trauma, research has shown links between self-blame appraisals and posttraumatic stress, dissociation, and depression symptoms (Daigneault, Tourigny, & Hebert, 2006;Feiring, Taska, & Lewis, 1998); self-blame appraisals and internalizing symptoms (Kerig, 1998); guilt appraisals and posttraumatic stress symptoms (Kletter, Weems, & Carrion, 2009); and shame appraisals and depression symptoms (Feiring et al, 1998). Literature in both adult and youth interpersonal trauma thus suggests the potential relevance of a wide range of appraisals including betrayal, self-blame, alienation, and shame, associated with different forms of trauma-related distress including posttraumatic stress, dissociation, and depression symptoms.…”
Section: Prior Research On Posttrauma Appraisals and Trauma-related Dmentioning
confidence: 93%
“…The literature on adults exposed to different forms of interpersonal trauma has shown links between shame appraisals and posttraumatic stress symptoms (Andrews, Brewin, Rose, & Kirk, 2000;Beck et al, 2011;La Bash & Papa, 2013;Wilson et al, 2011); self-blame appraisals and depression symptoms (Flicker, Cerulli, Swogger, & Talbot, 2012;Hassija & Gray, 2012;Hazzard, 1993;Kaysen, Scher, Mastnak, & Resick, 2005); betrayal appraisals and dissociation symptoms (DePrince et al, 2011;Smith & Freyd, 2013); and alienation appraisals and posttraumatic stress symptoms (DePrince et al, 2011). Among youth exposed to interpersonal trauma, research has shown links between self-blame appraisals and posttraumatic stress, dissociation, and depression symptoms (Daigneault, Tourigny, & Hebert, 2006;Feiring, Taska, & Lewis, 1998); self-blame appraisals and internalizing symptoms (Kerig, 1998); guilt appraisals and posttraumatic stress symptoms (Kletter, Weems, & Carrion, 2009); and shame appraisals and depression symptoms (Feiring et al, 1998). Literature in both adult and youth interpersonal trauma thus suggests the potential relevance of a wide range of appraisals including betrayal, self-blame, alienation, and shame, associated with different forms of trauma-related distress including posttraumatic stress, dissociation, and depression symptoms.…”
Section: Prior Research On Posttrauma Appraisals and Trauma-related Dmentioning
confidence: 93%
“…If the A2 criterion is to be retained in DSM-V, then, for young children, there should be strong consideration of including fears of harm to, or from, a primary caregiver. Although currently an associated feature of PTSD, exposure-related intense negative emotions, (e.g., shame and guilt) are strongly associated with PTSD severity in school-aged children and adolescents (Deblinger & Runyon, 2005;Joseph, Hodgkinson, Yule, & Williams, 1993;Kletter, Weems, & Carrion, 2009;Pynoos et. al., 1987), and reflect salient developmental challenges and potential etiologic factors.…”
Section: Criteria A1 and A2mentioning
confidence: 99%
“…Guilt over failure to prevent or stop violence has been associated with PTSD severity among child victims of interpersonal violence [30]. The relationship between exposure to IPV and children's post-traumatic symptoms seems especially strong, but fewer studies that measure PTSD have been performed and more research is required [1].…”
Section: Introductionmentioning
confidence: 99%